2000
DOI: 10.1042/bj3520725
|View full text |Cite
|
Sign up to set email alerts
|

Unique kinetics of nicotinic acid–adenine dinucleotide phosphate (NAADP) binding enhance the sensitivity of NAADP receptors for their ligand

Abstract: Nicotinic acid-adenine dinucleotide phosphate (NAADP) is a novel and potent Ca# + -mobilizing agent in sea urchin eggs and other cell types. Little is known, however, concerning the properties of the putative intracellular NAADP receptor. In the present study we have characterized NAADP binding sites in sea urchin egg homogenates. [$#P]NAADP bound to a single class of high-affinity sites that were reversibly inhibited by NaCl but insensitive to pH and Ca# + . Binding of [$#P]NAADP was lost in preparations that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 23 publications
5
37
0
Order By: Relevance
“…Radioligand binding studies further suggested that NAADP did not bind to the same site as inositol trisphosphate and cyclic ADP-ribose [15;16]. Bizarrely, NAADP appeared to bind its target in a non-reversible manner [15;17;18] at least in the presence of physiological K + concentrations [19]. This binding site, however, was clearly related to the calcium permeable channel targeted by NAADP, as evidenced by the similar rank order of potency of NAADP analogues for competing with radio-labelled NAADP [20] and for mediating both calcium release and inactivation [21].…”
Section: Naadp Activates a Novel Channelmentioning
confidence: 99%
“…Radioligand binding studies further suggested that NAADP did not bind to the same site as inositol trisphosphate and cyclic ADP-ribose [15;16]. Bizarrely, NAADP appeared to bind its target in a non-reversible manner [15;17;18] at least in the presence of physiological K + concentrations [19]. This binding site, however, was clearly related to the calcium permeable channel targeted by NAADP, as evidenced by the similar rank order of potency of NAADP analogues for competing with radio-labelled NAADP [20] and for mediating both calcium release and inactivation [21].…”
Section: Naadp Activates a Novel Channelmentioning
confidence: 99%
“…Radioligand binding studies employing [ 32 P]NAADP support the idea that NAADP acts on a fundamentally different Ca 2+ releasing channel from those gated by InsP 3 or cADPR. Binding of radiolabelled NAADP to sea urchin egg homogenate membranes is highly specific [13,31,32] and is unaffected by InsP 3 or cADPR [13,31]. Binding studies have revealed another peculiar property of the NAADP receptor where NAADP binds to its receptor in an essentially irreversible manner in the sea urchin egg homogenates [13,31,32].…”
Section: Distinct Properties Of Naadpmentioning
confidence: 99%
“…Binding of radiolabelled NAADP to sea urchin egg homogenate membranes is highly specific [13,31,32] and is unaffected by InsP 3 or cADPR [13,31]. Binding studies have revealed another peculiar property of the NAADP receptor where NAADP binds to its receptor in an essentially irreversible manner in the sea urchin egg homogenates [13,31,32]. In mammalian systems, however, [ 32 P]NAADP binding to membrane preparations from rat brain [31], rat heart [25] and MIN‐6 cells [10] is reversible.…”
Section: Distinct Properties Of Naadpmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown previously that, in vitro , NAADP binds to the sea urchin receptor in an irreversible manner under conditions mimicking the cellular environment ( Billington & Genazzani, 2000 ; Patel et al ., 2000 ; Dickinson & Patel, 2003 ). To investigate whether the triazine dyes displayed a similar property, sea urchin egg homogenates were pretreated for 20 min with concentrations of NAADP or dye that, in competition assays, displaced more than 90% of the [ 32 P]NAADP.…”
Section: Resultsmentioning
confidence: 99%